Conducting systematic literature reviews mediated by the Parsif.al Tool: potentials and limitations - Mauricio, Gustavo Carvalho (2025)
This article addresses the conduction of systematic literature reviews (SLR) mediated by the Parsif.al tool, highlighting its potentials and limitations. SLR is fundamental in scientific research, providing a structured and replicable synthesis of evidence. The study describes the stages of SLR — planning, conduction, and documentation — and emphasizes the importance of rigorous protocols to ensure transparency and reduce bias. Parsif.al is presented as an online, collaborative tool that facilitates SLR management, from defining criteria and selecting databases to data analysis. Despite its advantages, such as organization and automation, Parsif.al has limitations, such as the lack of advanced analyses and the need for complementary tools. It is concluded that, while valuable, the tool should be used in conjunction with the researchers' critical judgment to ensure the robustness of the review.